Job Satisfaction, Turnover Intention and Work Performance in Chinese Family Enterprises - Shu, Xiaobin; Gong, Yeming; Xiong, Jie; Hu, Xin (Management international / International Management / Gestiòn Internacional, 2018)
Based on the analysis of survey data of 121 family enterprises in China, we find that the relationship between job satisfaction and turnover intention is insignificant for family members, but significant for non-family members. Moreover, our findings also indicate that the effect of job satisfaction on work performance is less salient for family members, but more significant for non-family members. Our results further show that managerial positions moderates the main effects. This paper enriches the literature of family business by examining the importance of family membership and managerial position in the governance of family enterprises in an emerging country.